General practitioners and sickness certification for injury in Australia - Mazza, D.; Brijnath, Bianca; Singh, N.; Kosny, A.; Ruseckaite, R.; Collie, A. (BioMed Central Ltd., 2015)
© 2015 Mazza et al. Background: Strong evidence supports an early return to work after injury as a way to improve recovery. In Australia, General Practitioners (GPs) see about 96 % of injured workers, making them the main gatekeepers to workers' entitlements. Most people with compensable injuries in Australia are certified as "unfit to work" by their GP, with a minority of patients certified for modified work duties. The reasons for this apparent dissonance between evidence and practice remain unexplored. Little is known about the factors that influence GP sickness certification behaviour in Australia. The aim of this study is to describe the factors influencing Australian GPs certification practice through qualitative interviews with four key stakeholders. Methods: From September to December 2012, 93 semi-structured interviews were undertaken in Melbourne, Australia. Participants included GPs, injured workers, employers and compensation agents. Data were thematically analysed. Results: Five themes describing factors influencing GP certification were identified: 1. Divergent stakeholder views about the GP's role in facilitating return to work; 2. Communication between the four stakeholder groups; 3. Conflict between the stakeholder groups; 4. Allegations of GPs and injured workers misusing the compensation system and 5. The layout and content of the sickness certificate itself. Conclusion: By exploring GP certification practice from the perspectives of four key stakeholders, this study suggests that certification is an administrative and clinical task underpinned by a host of social and systemic factors. The findings highlight opportunities such as practice guideline development and improvements to the sickness certificate itself that may be targeted to improve GP sickness certification behaviour and return to work outcomes in an Australian context.